HUMAN RESOURCES MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION - Rita Pusvitasari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study analyzes the importance of human resource management in schools by focusing its analysis on human resource management in improving the quality of education at Al-Islam Krian High School, Sidoarjo, East Java. The education system at every level relies heavily on human resources for the implementation of its programs. The success of education in schools is determined by the principal's success in fostering and developing educators and education personnel in schools to improve the quality of education. This research uses a qualitative approach with the type of case study. Data collection techniques are carried out through; observation, interviews, and documentation. The results showed that planning in improving the quality of education was carried out by analyzing human resource needs and mapping positions according to the school's vision, mission, and goals, making job descriptions and job specifications. Existing human resources are then fostered and trained to improve the quality of their resources by those targeted by educational institutions.